Analisis pengenaan tarif dan perhitungan pajak air permukaan pada wajib pajak berdasarkan Perda Sulut Nomor 5 Tahun 2018 (Studi kasus pada Badan Pendapatan Daerah Provinsi Sulawesi Utara) - Taroreh, Eric Ignatius; Runtu, Treesje; Mintalangi, Syermi S. E. (Riset Akuntansi dan Portofolio Investasi, 2024)
Local tax is a type of tax that the local government is entitled to manage and collect from taxpayers who live in a region. Surface water tax is a type of provincial tax imposed on taxpayers who take and utilise surface water. This research will determine how surface water tax rates are imposed and how surface water tax is calculated for taxpayers in accordance with North Sulawesi Province Regional Regulation No. 5 of 2018 concerning Regional Taxes. This research employs a qualitative descriptive approach to qualitative research. The results of this study definitively show that the Manado, Minahasa, Bitung, and Tomohon regions comply with the Regional Regulation of North Sulawesi Province No. 5 of 2018 on the imposition of surface water tax rates and calculations to taxpayers. However, there is clear evidence that the UPTD made a calculation error in relation to one of the surface water taxpayers in the Bitung area in 2021-2022. This has resulted in a discrepancy between the calculation results presented in this research and those provided by the UPTD.